1997
DOI: 10.1021/bp970025a
|View full text |Cite
|
Sign up to set email alerts
|

Preparative Concentration and Size Fractionation of DNA by Porous Media Using a Combination of Flow and Low Electric Field Strength

Abstract: The retention of DNA by porous media during chromatography with an applied axial electric field was investigated. DNA was retained by negative electric fields in columns packed with Sephadex G-75 and G-25. A negative field was defined as the electric field orientation in which the direction of electrophoresis was opposing the direction of buffer flow (positive electrode at the column inlet). A positive field was not effective at retaining the DNA. The electric field strength required to retain the DNA was depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 12 publications
(18 reference statements)
1
21
0
Order By: Relevance
“…Operation of the EC systems has been described previously [7]. Briefly, water-jacketed columns (1.5´30 cm and 2.5´60 cm) were packed with the appropriate sizeexclusion resin.…”
Section: Ecmentioning
confidence: 99%
See 4 more Smart Citations
“…Operation of the EC systems has been described previously [7]. Briefly, water-jacketed columns (1.5´30 cm and 2.5´60 cm) were packed with the appropriate sizeexclusion resin.…”
Section: Ecmentioning
confidence: 99%
“…Cole [7] had previously observed that lower electric fields were needed to retain DNA in an EC column as the gel porosity increased. We have now confirmed the same trend in the case of proteins.…”
Section: Separation Of B-lg a And Bmentioning
confidence: 99%
See 3 more Smart Citations